(untitled) (Fiep Bulletin - online, 2013)
The objective of this study is to investigate the corporal rhythm; presenting the enabling structures that the citizen must differentiate and integrate to understand the composition of this. In this research we present the thoughts of some authors in what it says respect to the rhythm, and we relate these ideas with the capacitative structures that the rhythm composes: time, space and speed. Some authors only try to define the rhythm, others speak partially of its composition, but they do not understand the rhythm as being composed for the time, space and speed. With the result of this research, it is understood that for a significant education of the content rhythm in the lessons of Physical Education its composition must also be known and as the citizen carries through its understanding of these structures, therefore the superficiality with that is treated the content already does not take care of the educational necessities if we understand this discipline as knowledge area.